2021
DOI: 10.1111/ijlh.13670
|View full text |Cite
|
Sign up to set email alerts
|

Continuous reference curves for common hematology markers in the CALIPER cohort of healthy children and adolescents on the Sysmex XN‐3000 system

Abstract: Introduction: Clinicians and healthcare professionals rely heavily on health-associated standards, such as reference intervals (RIs), for appropriate laboratory test result interpretation. RIs are commonly partitioned into discrete age/sex bins based on statistical and/or clinical significance. In pediatric hematology, such partitioning does not adequately represent complex variation in analyte concentrations throughout maturation. The objective of this study was to establish continuous RIs for common hematolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…In order to put our generated results into context, we compared the results to RIs established in other projects. Here, we included results from the CALIPER studies 21 , 22 , 38 , the multi-center PEDREF project 13 , 14 , as well as RIs stated in the package inserts provided by the manufacturers 23 – 27 . The comparisons are shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In order to put our generated results into context, we compared the results to RIs established in other projects. Here, we included results from the CALIPER studies 21 , 22 , 38 , the multi-center PEDREF project 13 , 14 , as well as RIs stated in the package inserts provided by the manufacturers 23 – 27 . The comparisons are shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The CALIPER project has established age- and sex-specific RIs for children from birth to adulthood for over 170 biomarkers using population-based methods. For a subset of these, continuous RIs are reported as well 21 , 22 , 37 , 38 . However, due to a limited number of samples from healthy neonates and young children, and the extensive dynamics during these early stages of life, the first 6 or 12 months of life are excluded.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, future longitudinal study designs should consider simultaneously comparing discrete and continuous haematological reference intervals to ascertain which better reflect the dynamics in pregnancy. Recently, the CALIPER cohort study [23] concluded that continuous reference intervals better represented the complex changes in haematological variables within the paediatric age range instead of the traditionally used discrete partitioning of these reference intervals. A similar data exploration would likely improve haematological test interpretation as well as improve intra-partum and post-partum decision making process.…”
Section: Plos Onementioning
confidence: 99%